2005
DOI: 10.1159/000085541
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocorticotropin/Cortisol and Arginine-Vasopressin Secretory Patterns in Response to Ghrelin in Normal Men

Abstract: This study was performed in order to establish the secretory patterns and the possible relationships between the adrenocorticotropin (ACTH)/cortisol and arginine vasopressin (AVP) responses in normal men to the systemic administration of ghrelin, an endogenous ligand for the growth hormone secretagogue receptor. For this purpose, a bolus of 1 µg/kg ghrelin was injected intravenously in 9 normal men. AVP, ACTH and cortisol significantly rose in response to ghrelin injection; however, in all subjects the AVP ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Thus, native AG stimulates AVP release from rat posterior pituitary gland, probably via an indirect action mediated by NPY neurons (Ishizaki et al 2002, Wren et al 2002. Notably, AG-induced ACTH release has also been suggested to be mediated by the AG action on AVP secretion, because the AG-induced AVP rise precedes the increase in ACTH and cortisol levels in response to AG injection in healthy men (Coiro et al 2005). On the other hand, the relationship between the OT and ghrelin systems has not been fully elucidated.…”
Section: Posterior Pituitary Hormonesmentioning
confidence: 98%
“…Thus, native AG stimulates AVP release from rat posterior pituitary gland, probably via an indirect action mediated by NPY neurons (Ishizaki et al 2002, Wren et al 2002. Notably, AG-induced ACTH release has also been suggested to be mediated by the AG action on AVP secretion, because the AG-induced AVP rise precedes the increase in ACTH and cortisol levels in response to AG injection in healthy men (Coiro et al 2005). On the other hand, the relationship between the OT and ghrelin systems has not been fully elucidated.…”
Section: Posterior Pituitary Hormonesmentioning
confidence: 98%
“…The mechanism underlying GHRP-2's stimulation of ACTH release remains controversial. Previous studies in humans suggested that GHRP's ACTH-releasing activity may be mediated via CRH and/or AVP [3,5,7,11], or independent on both peptides [12]. Very recently, Kamoi et al [13] showed that GHRP-2 does not stimulate AVP secretion.…”
Section: Provocative Tests For Acth and Cortisol Secretionmentioning
confidence: 99%
“…Since GhRp-2 has a role as a ghrelin receptor agonist, the GhRp-2 test could provide a non-osmotic stimulus for AVp secretion. coiro et al demonstrated that ghrelin stimulated AVp secretion in healthy men with fasting [10]. there were no significant differences in sex, age, and bMi between the two studies.…”
Section: Acknowledgmentsmentioning
confidence: 88%
“…ten healthy men, aged 24 to 34 years (mean age, 30 ± 0.9 years), with bMis ranging from 20.0 to 26.7 (mean, 22.0 ± 0.7) kg/m 2 , were studied based on the method of coiro et al [10]. they had received no drugs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation